Effect of short-term (4 weeks) low-calorie diet induced weight loss on beta-cell function in overweight normoglycemic subjects: A quasi-experimental pre-post interventional study - Monica Peter; Mithra Balaji; Joe Varghese; Sam Marconi; Yesudhas Sudhakar; Felix Jebasingh; Padmanaban Venkatesan (Metabolism Open, 2025)
Introduction: Diabetes in South Asians is driven primarily by impaired beta-cell function. When challenged with a high-calorie diet, this can result in metabolically unfavourable fat accumulation, which in turn worsens beta-cell function, thus constituting a vicious cycle. The investigators hypothesized that short-term mild-to-moderate weight loss induced by calorie restriction could break the cycle, resulting in significant improvements in beta-cell function. The objective of this study, therefore, was to evaluate the efficacy of a short-term weight loss program on body composition and beta-cell function. Methods: As part of this quasi-experimental pre-post intervention study, 23 overweight normoglycemic participants underwent a low-calorie dietary intervention (∼1500 kcal/day) for a period of 4 weeks. Beta-cell function and insulin sensitivity were measured with a mixed meal challenge test (oral minimal model of glucose) before and after the intervention period. Changes in anthropometric parameters and body composition were also measured. The study was registered prospectively with the Clinical Trials Registry of India - CTRI/2023/04/051807 (https://ctri.nic.in/) Results: Among the 23 participants in the study, 21 adhered to the intervention. The average weight loss was 3.5 % with an 11 % reduction in trunk fat mass. Beta-cell function, as measured by disposition index, increased by 128 % on average. Robust linear regression analysis showed that beta-cell function improved by 23 % for 1 % weight loss (P = 0.024). Conclusion: A short-term mild-to-moderate weight loss in overweight normoglycemic subjects effectively improved their beta-cell function.